PENERAPAN MODEL PEMBELAJARAN DENGAN METODETWO STAY TWO STRAY (TS-TS) PADA MATA DIKLAT TEKNIK MESIN DI SMK MUHAMMADIYAH SUMOWONO - -, SURIANTO (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
This study directed forDetermine the implementation of Mechanical Engineering with a method of learning two stay two stray (TS-TS) at SMKMuhammadiyah Semarang regency Sumowono.Determine the success of Mechanical Engineering with a method of learning two stay two stray (TS-TS) on quality and learning outcomes learners in vocational Muhammadiyah Sumowono Semarang District.And,know the obstacles and weaknesses in Mechanical Engineering with a method of learning two stay two stray (TS-TS) at SMKMuhammadiyahSumowono Semarang regency.This study was a qualitative research. The Methods of collecting data used interviews, the participation of observation, and the triangulation of data. Analysis of the data used the interactive method. The Validity of data used triangulation methods, and the learning of Implementation Plan Analysis Mechanical Engineering with two stay two stray methods (TS-TS) at SMKMuhammadiyah Sumowono done systematically. The prior to implementing the learning activities of mechanical engineering studies teachers prepare the necessary equipment such as forming groups, arranging seating, setting up the learning, teaching materials to be used, learning media and named groups. The Teachers finished with some reflection activities with learners who analyzed the results of the discussion. Mechanical Engineering Learning used two stay two stray (TS-TS) at SMKMuhammadiyah Sumowono could be said to be successful when viewed from the aspect of quality and learning outcomes. Quality is evident from the interactive learning process conducted by teachers and learners. Mechanical Engineering Barriers to learning usedtwo stay two stray (TS-TS) at this school from the learner factors, the time, the scope of the material, and learning spaces.Learning time reduced because equipments used to prepare teachersÂ used ICT and learners to organize the space and draw up a table and chairs. Not all materials can be provided by using two stay two stray (TS-TS) so that the teacher must pick and choose appropriate materials for learning. The school does not have a dedicated space for group activities so that they use the regular classroom where the arrangement of office is seen is not maximized.Â .Keywords: learning, two stay two stray (TS-TS), mechanical engineering